Several forms of SARS-CoV-2 RNA can be detected in wastewaters: Implication for wastewater-based epidemiology and risk assessment. (15th June 2021) - Wurtzer, S.; Waldman, P.; Ferrier-Rembert, A.; Frenois-Veyrat, G.; Mouchel, J.M.; Boni, M.; Maday, Y.; Marechal, V.; Moulin, L.; ,
Highlights: The potential infectivity of SARS-CoV-2 excreted in wastewater could be preserved during transit time in wastewater. Temperature of raw wastewater was a key factor for decay of virus infectivity. Total viral RNA genome is stable for 7 days at least. SARS-CoV-2 RNA can be found in different states: infectious particles, non-infectious but protected genome and free RNA. Integrity assay could allow a better estimation of infectious risk associated to exposure to contaminated wastewaters. Abstract: The ongoing global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a public health emergency of international concern. Although SARS-CoV-2 is considered to be mainly transmitted by inhalation of contaminated droplets and aerosols, SARS-CoV-2 is also detected in human feces and to a less extent in urine, and in raw wastewaters (to date viral RNA only) suggesting that other routes of infection may exist. Monitoring SARS-CoV-2 genomes in wastewaters has been proposed as a complementary approach for tracing the dynamics of virus transmission within human population connected to wastewater network. The understanding on SARS-CoV-2 transmission through wastewater surveillance, the development of epidemic modeling and the evaluation of SARS-CoV-2 transmission from contaminated wastewater are largely limited by our knowledge on viral RNA genome persistence and virus infectivity preservation in such an environment. Using an integrity based RT-qPCR assay this study led to the discovery that SARS-CoV-2 RNA can persist under several forms in wastewaters, which provides important information on the presence of SARS-CoV-2 in raw wastewaters and associated risk assessment. Graphical abstract: Image, graphical abstract